Inverse Vulcanization of Styrylethyltrimethoxysilane–Coated Surfaces, Particles, and Crosslinked Materials. Issue 42 (5th October 2020) - Scheiger, Johannes M.; Direksilp, Chatrawee; Falkenstein, Patricia; Welle, Alexander; Koenig, Meike; Heissler, Stefan; Matysik, Jörg; Levkin, Pavel A.; Theato, Patrick
Abstract: Sulfur as a side product of natural gas and oil refining is an underused resource. Converting landfilled sulfur waste into materials merges the ecological imperative of resource efficiency with economic considerations. A strategy to convert sulfur into polymeric materials is the inverse vulcanization reaction of sulfur with alkenes. However, the materials formed are of limited applicability, because they need to be cured at high temperatures (>130 °C) for many hours. Herein, we report the reaction of elemental sulfur with styrylethyltrimethoxysilane. Marrying the inverse vulcanization and silane chemistry yielded high sulfur content polysilanes, which could be cured via room temperature polycondensation to obtain coated surfaces, particles, and crosslinked materials. The polycondensation was triggered by hydrolysis of poly(sulfur‐ r ‐styrylethyltrimethoxysilane) (poly(Sn ‐ r ‐StyTMS) under mild conditions (HCl, pH 4). For the first time, an inverse vulcanization polymer could be conveniently coated and mildly cured via post‐polycondensation. Silica microparticles coated with the high sulfur content polymer could improve their Hg 2+ ion remediation capability. Abstract : Marrying inverse vulcanization and silane chemistry yields solution‐processable high sulfur content polysulfide‐alkoxysilanes, which could be cured via polycondensation. With this strategy, coated surfaces and particles as well as crosslinked materials can be obtained. This method extends the applicability and control of materials prepared via inverse vulcanization.